HOW BRAND AWARENESS AND PRICING STRATEGY SHAPE CONSUMER DECISIONS: AN EVIDENCE FROM INDONESIAN LOCAL FASHION BRAND - Putri Ermawan, Amanda; Mubarok, Dadan Abdul Aziz (Universitas Muhammadiyah Tangerang, 2025)
Indonesia's fashion industry is growing dynamically with cultural diversity and creativity, but amid fierce competition, the apparel industry is in decline in 2023. This phenomenon encourages the need to analyze factors that influence consumer purchasing decisions, especially brand awareness and price, as a competitive strategy. This study aims to analyze the influence of these two variables on the purchase decision of OR Chip Best Brand Collection products, as well as provide business recommendations based on empirical findings. The research method uses a quantitative approach with linear regression analysis based on survey data of 150 fashion consumer respondents. The results of the study prove that both brand awareness and price have a significant and positive effect on purchase decisions, with brand awareness as the dominant factor. The novelty of the research lies in its contextual approach to local fashion brands in the face of intense industry competition. The contribution of this research provides practical implications for business actors in improving brand equity-based marketing strategies and competitive pricing, while maintaining product quality.